2016
DOI: 10.1007/s00221-016-4636-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving postural control by applying mechanical noise to ankle muscle tendons

Abstract: The application of subthreshold mechanical vibrations with random frequencies (white mechanical noise) to ankle muscle tendons is known to increase muscle proprioceptive information and to improve the detection of ankle movements. The aim of the present study was to analyze the effect of this mechanical noise on postural control, its possible modulation according to the sensory strategies used for postural control, and the consequences of increasing postural difficulty. The upright stance of 20 healthy young p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 37 publications
2
26
2
Order By: Relevance
“…For instance, during a sensory conflict task (i.e., moving visual surrounding), addition of mechanical noise improved postural control in older adults (Dettmer et al, 2015) but no effects were observed in young adults (Keshner et al, 2014;Dettmer et al, 2015). On the other hand, no effects of SR mechanical stimulation on postural control were obtained during translation of support surface in both young and older adults (Borel and Ribot-Ciscar, 2016;Dettmer et al, 2016). Considering that SR effects on motor control still need to be further understood, the goal of the present research was to verify if there are age-related differential SR effects when electrical noise is applied during tasks with different sensory (visual) demands.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, during a sensory conflict task (i.e., moving visual surrounding), addition of mechanical noise improved postural control in older adults (Dettmer et al, 2015) but no effects were observed in young adults (Keshner et al, 2014;Dettmer et al, 2015). On the other hand, no effects of SR mechanical stimulation on postural control were obtained during translation of support surface in both young and older adults (Borel and Ribot-Ciscar, 2016;Dettmer et al, 2016). Considering that SR effects on motor control still need to be further understood, the goal of the present research was to verify if there are age-related differential SR effects when electrical noise is applied during tasks with different sensory (visual) demands.…”
Section: Introductionmentioning
confidence: 96%
“…Participants from group 2 performed also the sham test, i.e., they were asked to stand still for three additional 50 s trials where the first and the last trial were without any feedback (V − T − ; T9-T11), and the second trial with the sham feedback (V − T +S ; T10), i.e., a vibrotactile feedback where the vibration intensity was not related to the actual CoM oscillations (see Vibrotactile Feedback Control section). The rationale of testing the effect of sham feedback was to verify if measurable sway changes observed in our experiment were due (1) to the informational content of the supplemental vibrotactile feedback or (2) to a mere effect of vibration acting as noise and increasing the perceptive thresholds as in Dhruv et al (2002), Liu et al (2002), Janssen et al 2010, Magalhães and Kohn (2011), Borel and Ribot-Ciscar (2016), and Kwak et al (2016). In the latter case, we expected that changesand specifically a reduction-of the postural sway during the exposure to the synchronized informative feedback, would have been maintained during the exposure to the unsynchronized sham feedback.…”
Section: Testmentioning
confidence: 96%
“…The lack of effect on the postural sway of the two different encodings methods described above could be due to the exposure to vibration, with different directional effects because the vibrator motors being located on the front/back of the participants, i.e., the vibration was provided along the AP direction. In fact it is well-known that also a low-level noise vibrotactile stimulation increase the detection of the stimuli, leading to improvements in postural control (Gravelle et al, 2002;Priplata et al, 2002Priplata et al, , 2003Magalhães and Kohn, 2011;Borel and Ribot-Ciscar, 2016;Kwak et al, 2016). To verify whether or not the participants in this experiment integrated their neural control of the informational content encoded in the vibration, we added a trial where the participants of group 2 where exposed to sham feedback.…”
Section: The Sham Feedback Led To Different Sways Patterns Than the Vmentioning
confidence: 99%
See 2 more Smart Citations